Working Efficiency of Contrasting Genders under Eustress, Distress, Hyper-Stress, and Hypo-Stress - Faizan, Riffat; Haque, Adnan ul (Prabandhan: Indian Journal of Management, 2019)
The aim of the study was to investigate the types of stressors affecting the working efficiency of distinctive genders in Pakistan. A total of 281 employees (Males = 140 and Females = 141) working in the IT sector were recruited through stratified (probability) and purposive and convenience (non-probability) sampling techniques. An online matrix based 5-point scale survey was circulated through gatekeepers. The results showed that younger females had higher ‘eustress’; whereas, males had higher ‘distress’ due to less moral and emotional support. Overall, males were more vulnerable to stress as compared to the females. Females effectively used social support in contrast to their counterparts. Personal stressors frequently distressed females; while, organizational stressors distressed males. The behavioural and physiological reactions resulted from hyper-stress among females; whereas, psychological reactions were shown by males under hypo-stress. Job role affected the working efficiency of non-managers more as compared to the managers. Adequate usage of personal resources was reported to be effective for coping with the job-related stress.